CP-142 One stop dispensing: Medication-economic perspectives on self-administrating elective gastric surgery patients. (14th February 2016) - Andersen, MB; Yassin, ST; Thinglev, T; McNulty, HBØ
Abstract : Background: The patient role is changing to include more patient involvement, control and empowerment. To accommodate this new patient profile, the medication system, one stop dispensing (OSD), has been tested. Patients' own drugs (POD) are used during hospitalisation and patients administrate their own medication when it is considered safe. Purpose: To study the economic perspectives of the OSD system of self-administrating elective gastric surgery patients with a focus on medicine. Material and methods: The pilot project was performed from March to June 2015. Pre-surgery pharmacy staff recorded a medication history and asked the patient to bring their POD at admission. Pharmacy staff performed quality assurance of POD, and medicine was placed in a bedside locker. Time released from medicine dispensing was spent on quality assurance of POD. If POD shortages were experienced or new prescriptions were needed (eg, painkillers), pharmacy staff supplied medications in small original packages. Patients were discharged with all prescribed medications to cover 10 days of treatment. In the traditional medication system, POD are not used and patients are discharged with medications to cover only 2 days (in pillbox). The pharmacy's direct medicines cost price was used to compare the medication-economics between the OSD system and the traditional medication system. Results: 42 consecutive self-administrating elective gastric surgery patients (70% female, mean age 53 years (range 22–98)) were included. On average, patients used 2.1 (range 0–9) prescribed medicines (in total 89). 77 of the 89 (87%) prescribed medicines and 24 food supplements were brought to the hospital in good conditions. On average, the OSD system had an additional medication cost of 1.9€ per patient compared with the traditional medication system. The additional OSD system cost was purely attributable to lack of price negotiation on small medicine packages. In this patient group, medicine supplied once in small original packages covered the entire hospital stay and 10 days after discharge. OSD medication costs were therefore unaffected by the increased medication coverage rate from 2 to 10 days after discharge. Conclusion: The OSD system had a small additional medication cost compared with the traditional medication system. In the future, the focus should be on negotiating prices for small packages. Additionally, it will be necessary to investigate if the OSD system saves time and supports patient safety. No conflict of interest.